Quill and Cross in the Borderlands : Sor María de Ágreda and the Lady in Blue, 1628 to the Present - Nogar, Anna M., 1977-; Nogar, Anna M., 1977- (Book collections on Project MUSE., 2018)
Introduction : a literary protomissionary in the borderlands -- Seventeenth-century spiritual travel to New Mexico : a miracle narrative in text -- Sor María's rise as mystical writer and protomissionary in early modern Spain -- "Como si fuera natural de Mexico" : publication, reading, and interpretation of Sor Mariua's writing in colonial Mexico -- "Aquella voz de las conversiones" : writer and missionary on the new Spanish frontier -- Blue lady of lore : the lady in blue narrative and Sor María in the folklore of the American Southwest -- Sor María and the Lady in Blue in contemporary cultural imagination -- Conclusion : quill and cross in the borderlands